2013
DOI: 10.3233/ch-2012-1619
|View full text |Cite
|
Sign up to set email alerts
|

The hemorheological safety of pulsed electromagnetic fields in postmenopausal women with osteoporosis in southwest China: A randomized, placebo controlled clinical trial

Abstract: Apart from medications, pulsed electromagnetic fields (PEMFs) are used to treat osteoporosis nowadays. However studies on hemorheological safety of PEMFs were scarce. This randomized, placebo controlled clinical trial assessed whether PEMFs could lead to significant hemorheological changes. Fifty-five postmenopausal women were randomly assigned to receive placebo or PEMFs. Venous blood samples were collected at baseline and after treatment to measure 14 hemorheological determinants. Independent samples t-test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In various animal models of osteoporosis, PEMF was associated with higher BMD, bone strength, and less deterioration of bone microarchitecture [Jing et al, , , , ]. Clinical studies with osteoporotic patients have also indicated that PEMF can increase BMD, alleviate pain, and improve quality of life without side effects [Liu et al, ,]. In our previous studies with rats, PEMF appeared to have positive effects in ovariectomy‐induced osteoporosis [Zhou et al, , ] and streptozotocin‐induced diabetic osteopenia [Zhou et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…In various animal models of osteoporosis, PEMF was associated with higher BMD, bone strength, and less deterioration of bone microarchitecture [Jing et al, , , , ]. Clinical studies with osteoporotic patients have also indicated that PEMF can increase BMD, alleviate pain, and improve quality of life without side effects [Liu et al, ,]. In our previous studies with rats, PEMF appeared to have positive effects in ovariectomy‐induced osteoporosis [Zhou et al, , ] and streptozotocin‐induced diabetic osteopenia [Zhou et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…PEMF devices were conducted using an XT-2000B therapeutic stimulator (Tianjin xtmed, Tianjin, China). According to the manufacturer's instructions and statement, as well as the purpose of the study, it generated time-varying fields consisting of bursts of asymmetric pulses as in previous studies [16]. According to the manufacturer's instructions and statement, as well as the purpose of the study, it generated time-varying fields consisting of bursts of asymmetric pulses.…”
Section: 2mentioning
confidence: 94%
“…Pulsed electromagnetic field (PEMF) therapy is a promising alternative to drug‐based interventions for osteoporosis. In previous studies, we demonstrated that PEMF therapy increases bone mineral density (BMD), alleviates pain, improves the quality of life of patients with osteoporosis, and has a good safety profile [Liu et al, ,]. PEMF has been shown to be effective in animal models of osteoporosis [Jing et al, , , , ].…”
Section: Introductionmentioning
confidence: 99%